Cognitive Knowledge Management (CKM): preliminary exploration towards a unified theory (2019)
This article proposes a preliminar and theoretical exploration towards a novel and unified theory of knowledge management (KM) and knowledge management strategy (KMS) supported by cognitive science, its interdisciplinary nature and the success that it has had on disciplines that are closely related with the mind. The overall ambition of this exploration is to initiate a new, powerful and reinvigorated theoretical route that can be recommended for all knowledge-based organizations across industries, and that can get closer to the promises that knowledge management have had from its beginning in terms of increasing efficiency and cre- ation of value in organizations. The article begins by tracking down the motivation and origins of cognitive knowledge management (CKM), followed by a definition of the theory and its com- ponents, and concludes with some comments on the potential future of empirical research on the subject.